Pengolahan Limbah Cair Hotel Dengan Kombinasi Metode Elektrokoagulasi Dan Adsorpsi Menggunakan Karbosil - Lenny Warlina; Ilim Ilim; Wasinton Simanjuntak (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
This study was carried out to investigate treatment of hotel wastewater using a combination of electrocoagulation and adsorption using carbosil prepared from rice husk with pyrolysis method. Electrocoagulation was applied with the aim to remove natural organic matter in the sample, using aluminim as electrodes, with the particular purpose to study the effect of potentials. The treated water was then subjected to adsorption process at different contact times and the performance of the process was evaluated in term of the reduction of the absorbance at maximum wavelength. The performance of the method was defined in term of absorbance reduction at the maximum wavelength of 226 nm, which was determined by scanning the original sample at the wavelength ranging from 200 to 700 nm. According to literature, the maximum wavelength of 226 nm is commonly assigned to benzene structure, most likely from the Alkyl Benzene Sulfonate (ABS) used in detergents. The results obtained indicate that for electrocoagulation process, the highest reduction in the absorbance was achieved using potential of 10 volt. Adsorption process was found to result in the diminish of peak at 226 nm, reflecting that the organic pollutant associated with this wavelength has been completely removed from the water. Characterization of the carbosil using SEM technique revealed that the carbosil has practically homogeneous surface morphology, supporting its ability to adsorb the pollutants from the wastewater. Keywords: adsorption, carbosil, electrocoagulation, hotel wastewater